PSEUDOMONAS AERUGINOSA BIOPHIL FORMATION MECHANISMS AND ANTIBIOTIC RESISTANCE RELATING TO CURRENT ISSUES (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2026)
Pseudomonas aeruginosa is an opportunistic pathogen that forms biofilms and is highly resistant to antibiotics. This study investigated the steps of bifilm formation, the mechanism of quorum sensing, and the antibiogram profile using a novel approach. Crystal violet assay and MIC detection methods were used to determine the 72-hour biofilm density (OD 0.912) and 10–128-fold resistance to antibiotics. Furanone-AHL quorum sensing inhibitor was shown to have an 80% biofilm reduction effect. The results provide a basis for a biofilm-fighting strategy as a promising solution for QS-opponent therapy.